Analysis of Computational Fluid Dynamics on 3D Printing Propeller Design using Thermoplastic Material - Nurhidayanti; Muhammad Ikhsan; Muh. Abdillah (Department of Mechanical Engineering, Universitas Andalas, 2025)
The propeller is essential in generating thrust for various applications, from UAVS to ship propulsion and industrial ventilation. Propeller performance is greatly influenced by the characteristics of the fluid flow generated by the interaction between the propeller blades and the surrounding medium. 3D printing technology offers design flexibility and cost efficiency in propeller manufacturing. This study aims to analyse the effect of rotational speed variations on the performance of 3d printed propeller designs made of PLA. Simulation of Computational Fluid Dynamics (CFD) was used to evaluate the fluid flow velocity distribution, flow pattern, and flow type transition around the propeller. The results showed that the variation of rotational speed affects the fluid flow type, with low rotational speed producing laminar flow and high rotational speed producing transitional flow. This understanding is important for the optimisation of PLA 3D printing propeller design in improving efficiency and reducing noise.